2017
DOI: 10.1016/j.jchf.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Race-Related Differences in Left Ventricular Structural and Functional Remodeling in Response to Increased Afterload

Abstract: Background Chronic increasing in arterial afterload may be an important trigger for left ventricular (LV) remodeling and dysfunction that lead to heart failure (HF). Racial differences in the predisposition to HF are well described, but the underlying mechanisms remain unclear. Objective We evaluated the racial differences in arterial elastance (Ea), which reflects the arterial afterload faced by the LV, and its associations with cardiac structure and function. We hypothesize that the LV in blacks displays h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…However, the role of ethnicity in the pathogenesis of PPCM has never been studied. In the ARIC study, the authors showed that Black patients will preferentially develop eccentric hypertrophy rather than concentric hypertrophy, which is mainly presented by White patients . It has been suggested that eccentric remodelling in Black patients involves cardiomyocyte death and replacement fibrosis, which is characterized by an increase of collagen III .…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of ethnicity in the pathogenesis of PPCM has never been studied. In the ARIC study, the authors showed that Black patients will preferentially develop eccentric hypertrophy rather than concentric hypertrophy, which is mainly presented by White patients . It has been suggested that eccentric remodelling in Black patients involves cardiomyocyte death and replacement fibrosis, which is characterized by an increase of collagen III .…”
Section: Discussionmentioning
confidence: 99%
“…Higher arterial afterload combine with genetically determined myocardial hypersensibility among blacks may partly explain those racial divergences. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…However, the relative contribution of each of these factors remains poorly understood. Another contributing factor that may be critical in the development of LV dysfunction during sunitinib treatment is hypertension 20 , 21 , 22 . More specifically, it is not clear whether hypertension unmasks LV dysfunction or actually lowers the threshold for sunitinib cardiotoxicity.…”
mentioning
confidence: 99%